The level of serum creatine phosphokinase as a criterion of recovery in professional soccer players during the competitive period - V. Yu. Khaitin; S. V. Matveev; M. Yu. Grishin (National Electronic Information Consortium (NEICON), 2020)
Objective: the aim of this study was to evaluate the dynamics of the enzyme creatine phospokinase (CPK) in professional soccer players during the competitive period and to develop criteria and standards for the short and long-term adaptation of the athlete's body to physical exertion. Materials and methods: clinical and laboratory monitoring. During two seasons of the national championship 26 soccer players of high sports qualification (age: 26.7±3.1 years, height: 181.5±5.8 cm, fat content in the body: 9.9±1.7%) were examined. All athletes met the following criteria for inclusion in the study: participation in the pre-season, competition period; measurement of CPK level before the start of the season and at all time points after three games during the season; participation time - at least 75 minutes of the match (75-90 min/match); absence of muscle damage and complaints from the muscular system. Results: a twofold increase in the level of CPK was registered on the day after the match; a uniform decrease in the concentration of the enzyme was detected 60-72 hours after the match with the return of indicators to the pre-game level (p